Effectiveness and efficiency of adding drawing prompts to an interactive educational technology when learning with visual representations. (June 2018) - Wu, Sally P.W.; Rau, Martina A.
Abstract: This paper investigates whether prompting students to draw their own visual representations enhances students' learning from technology-based instructional activities with visual representations. Seventy-two undergraduate students were randomly assigned to receive an educational technology with (1) drawing prompts throughout instruction, (2) drawing prompts before and after instruction, or (3) no drawing prompts. We assessed learning outcomes with respect to instructional effectiveness and efficiency using immediate and delayed posttests. Results on instructional efficiency showed a significant advantage for drawing prompts. Results on instructional effectiveness showed an advantage at the delayed posttest for drawing prompts provided throughout instruction, compared to prompts before and after. Qualitative analyses suggest that adding drawing prompts throughout instruction promotes drawing quality. In sum, our findings expand theory by suggesting that drawing prompts facilitate visual sense making of concepts shown in visual representations. Furthermore, we provide practical recommendations on how best to implement drawing prompts with technology-based instructional activities. Highlights: Drawing prompts may help students learn concepts depicted in visual representations. We tested the effects of adding drawing prompts to an educational technology. Drawing prompts are effective on a delayed posttest, when provided frequently. Drawing prompts are efficient: they enhanced learning in less instructional time. For instructors, drawing prompts are low-effort and easy to add to instruction.